Resistividade elétrica de concretos compostos com cinza de lodo de ETA e calcário moído - Cocco, Marciana (2017)
Electrical resistivity, a property of the concrete that represents its resistivity to the passing of electric current, is important in terms of corrosion of reinforced concrete and, therefore, of the durability of the structures of reinforced concrete. The use of mineral additives in concrete matrices has been shown to be effective both in reducing the environmental impact caused by cement production and waste disposal and in improving properties related to the durability of structures. In this study, the performance of concrete with partial replacement of Portland cement by sludge ash from water treatment plant (WTPSA) and ground limestone before electrical resistivity was investigated. The definition of the mixtures followed a statistical design of the CCRD type, with WTPSA levels varying from 0% to 30%, concentrations of limestone between 0% and 15% and minimum and maximum water/binder (w/b) ratios of 0.35 and 0.65, in addition to a reference mix, with no mineral additions, with ratios of 0.35; 0.50 and 0.65. The assessment of the influence of variables in studies on electrical resistivity, through the response surface methodology, was carried out for the 7th, 14th, 28th, 56th and 91st days. The evolution of the electrical conductivity and potential of Hydrogen (pH) over time were also analyzed on the 7th, 28th and 91st days. The WTPSA, which was calcined in a muffle kiln at 700 ° C and ground in a ball mill for 1 h, became a mineral addition with high pozzolanic activity when in ternary mixtures with Portland cement and ground limestone. Better electrical resistivity results were obtained limestone content around 7.5% since the early ages. As for WTPSA, its content ranged from 0% in the early ages to 30% in older ages. The increase in its effect at each test age is an indication that WTPSA had an influence on the concrete microstructure. The reduction of electrical resistivity with increasing w/b ratio was greater at each age, being the factor with the greatest influence after 91 days. In time, both electrical resistivity, pH, and electrical conductivity decreased in all mixtures. According to the limits indicated by the CEB 192, low or negligible corrosion risk was reached with high levels of replacement of WTPSA and limestone in the mixtures. Moreover, for each relation w/b ratio, the greatest electrical resistivities were those of the mixtures with high levels of WTPSA and limestone in the proportion 2:1. Replacement of Portland cement by 15% of WTPSA and 7.5% of limestone proved to be efficient in reducing the risk of corrosion for both the environmental aggression classes defined by the NBR 12655 (ABNT, 2015) and on equal mechanical resistivity with concretes with no mineral additions. Additionally, a cement saving of more than 100 kg/m3 was observed for these same substitution contents in relation to their mixtures of the same compressive strength value.